Review of photovoltaic water pumping system research. (November 2020) - Shepovalova, Olga V.; Belenov, Alexander T.; Chirkov, Sergei V.
Abstract: Currently a considerable and the most economically justified potential of making the solar energy conversion more efficient and making the solar energy more attractive for consumers involves the coordination of the entire equipment from generation to consumption while considering all this equipment as a unified system and taking the degree of satisfaction of the consumer needs as the measure of efficiency. A photovoltaic water pumping system (PVWPS) is the first and one of few types of ground photovoltaic systems where the consumption equipment was always considered from the onset as part of the system. So a retrospective analysis of PVWPS research is of particular interest. This article contains the PVWPS research analysis beginning with the first research conducted in 1964–1966 to date. Discussed herein are the main problems that arose in the PVWPS development, operation, and optimization as well as options of their solution. Various areas of PVWPS improvement research were analyzed, including research involving photovoltaic array structure and photovoltaic modules interconnection; development and improvement of special structures of any components (pumps and invertors, etc.); improvement of photovoltaic array and electric motor interaction, electric motor and pump interaction against the backdrop of irradiance variation and in conjunction with consumption optimization and control improvement, to start with maximum power point tracing. It would make sense to aim further research involving cost reduction, productivity gain, and PVWPS service life extension at the expansion of the fields of PVWPS application, improvement of individual PVWPS components, and a more efficient use of water that is drawn. One of the prospective lines of PVWPS improvement and upgrading is to include them in the system of end user consumption equipment and assess the system efficiency not at the pump output and not in the point of end consumption equipment but after the water consumption. Studying PVWPS with the account of the fact that, in real conditions, the average output power of photovoltaic array depends not only on irradiance but also on the combined effect of all environmental conditions (climatic parameters, current state of atmosphere and air, surrounding objects, etc.) is of great importance, today.